What this pandemic reveals about the value of work - Robert Koepp (WZB Berlin Social Science Center, 2020)
The pandemic has revealed what kind of work deserves to be called ̮systemically importantŁ. Yet, as Robert Koepp argues, the struggle over labor conditions has only just begun.
Keywords: 300; contagious disease; Coronavirus; COVID-19; epidemic; precarious employment; occupation; relevance; remuneration; working conditions